Clinical characteristics and whole exome/transcriptome sequencing of coexisting chronic myeloid leukemia and myelofibrosis. Issue 6 (2nd May 2017) - Kandarpa, Malathi; Wu, Yi‐Mi; Robinson, Dan; Burke, Patrick William; Chinnaiyan, Arul M.; Talpaz, Moshe
Abstract: Myeloproliferative neoplasms (MPNs) are clonal hematopoietic stem cell (HSC) disorders that can be classified on the basis of genetic, clinical, phenotypic features. Genetic lesions such as JAK2 mutations and BCR‐ABL translocation are often mutually exclusive in MPN patients and lead to essential thrombocythemia, polycythemia vera, or myelofibrosis or chronic myeloid leukemia, respectively. Nevertheless, coexistence of these genetic aberrations in the same patient has been reported. Whether these aberrations occur in the same stem cell or a different cell is unclear, but an unstable genome in the HSCs seems to be the common antecedent. In an effort to characterize the underlying genetic events that might contribute to the appearance of more than one MPN in a patient, we studied neoplastic cells from patients with dual MPNs by next‐generation sequencing. We observed that most patients with two MPNs harbored mutations in genes known to contribute to clonal hematopoiesis through altered epigenetic regulation such as TET2, ASXL1/2, SRSF2, and IDH2 at varying frequencies (1%–47%). In addition, we found that some patients also harbored oncogenic mutations in N/KRAS, TP53, BRAF, EZH2, and GNAS at low frequencies, which probably represent clonal evolution. These findings support the hypothesis that hematopoietic cells from MPN patients harbor multiple genetic aberrations, some of which can contribute to clonal dominance. Acquiring mutations in JAK2/CALR/MPL or the BCR‐ABL translocation probably drive the oncogenic phenotype towards a specific MPN. Further, we propose that the acquisition of BCR‐ABL in these patients is frequently a secondary event resulting from an unstable genome.